Infants born into care in Scotland: Initial Findings - Raab, Gillian; McGhee, Janice; Macintyre, Cecilia (Scottish Centre for Administrative Data Research, 2020)
This report is one of the first outputs that uses linked data from the Looked after Children in Scotland data (LAC-S) to examine looked after children’s journeys. These data were made available to the research team in a secure environment that protects the privacy of all subjects. The report describes the patterns of care for infants who first became looked after in Scotland when under 1 year of age between 1st April 2008 and 31st July 2017. It includes details of all episodes of care up to the end of follow-up (31st July 2017).
Keywords: Infants; Care; Looked after children; Scotland